БИЛИАРНАЯ ПАТОЛОГИЯ И ЕЕ КЛИНИЧЕСКИЕ «МАСКИ». Часть 1 - Е. Ю. Еремина (Архивъ внутренней медицины)
The article gives systematicaly organized literature data and the author’s observations of different biliar tract disorder variants. The focus is on the comorbidity formation mechanisms analysis and the difficulties in differential diagnostics of various pathological conditions, associated with the gallbladder pathology and cholepatiae.